2010
DOI: 10.1504/ijbm.2010.031793
|View full text |Cite
|
Sign up to set email alerts
|

Contextual affect analysis: a system for verification of emotion appropriateness supported with Contextual Valence Shifters

Abstract: This paper presents a novel method for estimating speaker's affective states based on two contextual features: valence shifters and appropriateness. Firstly, a system for affect analysis is used to recognise specific types of emotions. We improve the baseline system with the analysis of Contextual Valence Shifters (CVS), which determine the semantic orientation of emotive expressions. Secondly, a web mining technique is used to verify the appropriateness of the recognised emotions for the particular context. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Most commonly, the system was used to analyze user input in human-agent interaction [1,3,4,15,23,24,25,26]. In particular, the analysis of user input was utilized in decision making support about which conversation strategy to choose (normal conversation or joke) [1], and in an automatic evaluation method for dialog agents [3].…”
Section: Russell's 2-dimensional Model Of Affectmentioning
confidence: 99%
See 3 more Smart Citations
“…Most commonly, the system was used to analyze user input in human-agent interaction [1,3,4,15,23,24,25,26]. In particular, the analysis of user input was utilized in decision making support about which conversation strategy to choose (normal conversation or joke) [1], and in an automatic evaluation method for dialog agents [3].…”
Section: Russell's 2-dimensional Model Of Affectmentioning
confidence: 99%
“…The system was most often evaluated on conversations, both between humans [1] and between human users and conversational agents [4,3,15,23,26]. In [1] Dybala et al showed that ML-Ask presents comparable answers to human annotators when annotating conversations between people of different age and status (in particular young students vs. middle-aged businessmen).…”
Section: Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of examples, the number of words, and the number of vocabularies are shown in Table 4. There are many approaches to estimating emotion from sentences using linguistic features [34][35][36][37][38]. These approaches often use machine learning methods such as neural networks for training the emotion estimators [39,40].…”
Section: Neural Networkmentioning
confidence: 99%